« De mes pleurs vous ne vous rirez plus » : le Cas Antiochus - Laurence Plazenet (Institut du Monde Anglophone, 2021)
Antiochus has a bad reputation. He is commonly considered to be a simpleton, whose whining hinders Bérénice from being anything but a mere elegiac and gallant drama. Yet, a new analysis of Antiochus makes it possible to suggest a completely different reading of his character. Although he is Bérénice’s paredros and is affected by the fundamental corruption of passions, he proves to be a perfect lover and to be the first one to accept the “separation”, which constitutes the very action of the play according to Racine. Thus, Antiochus foreshadows the journey from self-love to pure love that makes Bérénice a profoundly Augustinian and authentic tragedy that exposes the choice creatures have to make between the earthly city and the City of God. The tears that Antiochus so abundantly sheds in Bérénice eventually disclose that the play, years before Phèdre, contains strong echoes of the liturgical poem Dies Irae, and especially from its final stanza the Lacrimosa. This observation draws attention to the fact that Racine’s plays, at least from Britannicus on, are deeply marked by spiritual concerns. Influenced by the figurist exegesis used by the Messieurs of Port-Royal to decipher sacred as well as profane texts, and strongly nourished by Saint-Cyran’s thought, Racine investigates the case of the “old man”, who was both prone to philosophical impenitence and capable of feeling the raptures of love. A longtime wanderer, on the verge of leaving Rome and going back to the Middle East and its solitudes, Antiochus suddenly appears to be an outstanding and powerfully moving (“touchante,” says Racine) figure of a “renewed” man.